2018
DOI: 10.1007/s00268-018-4754-z
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Among Surgical Patients: A Systematic Review and Meta‐analysis

Abstract: Health literacy is the extent to which patients are able to understand and act upon health information. This concept is important for surgeons as their patients have to comprehend the nature, risks and benefits of surgical procedures, adhere to perioperative instructions, and make complex care decisions about interventions. Our review aimed to determine the prevalence of limited health literacy of the surgical patient population. A search of MEDLINE and EMBASE was performed from inception until January 14th 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 95 publications
(49 reference statements)
0
26
0
1
Order By: Relevance
“…Cognitive function, language barriers, health literacy, and other social determinants of health also significantly influence postoperative pain management and recovery [51,[80][81][82]. Validated health literacy assessments have been applied to surgical populations [83][84][85][86][87]. Prospective identification of these challenges, including the application of standardized cognitive and psychosocial assessments, can allow for appropriate preoperative referral, patient optimization, and future study of risk mitigation strategies [15,18,52,75,78,80,88].…”
Section: Patient Pain History Evaluation and Educationmentioning
confidence: 99%
“…Cognitive function, language barriers, health literacy, and other social determinants of health also significantly influence postoperative pain management and recovery [51,[80][81][82]. Validated health literacy assessments have been applied to surgical populations [83][84][85][86][87]. Prospective identification of these challenges, including the application of standardized cognitive and psychosocial assessments, can allow for appropriate preoperative referral, patient optimization, and future study of risk mitigation strategies [15,18,52,75,78,80,88].…”
Section: Patient Pain History Evaluation and Educationmentioning
confidence: 99%
“…Subgroups with increased risk of limited HL include older persons (Berkman et al, 2011) and people with low income (Jessup et al, 2017) and a low educational level (Protheroe et al, 2017). The results from a meta-analysis on the prevalence of HL among surgical patients ( n = 18,895) showed that 31.7% had limited HL (Roy et al, 2019). Similarly, a study reported that 39.4% of day surgery patients had limited HL skills, which were found to be associated with poorer quality of postoperative recovery (Halleberg Nyman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, a few closely related studies about the health literacy needs of surgical patients. One systematic review and meta-analysis reported heterogeneity in health literacy among surgical patients (Roy et al, 2019). A qualitative systematic review indicated a possible association between low health literacy and low comprehension of surgical procedures, and poor adherence to preoperative instructions (Oliveira, McCarthy, Wolf, & Holl, 2015).…”
Section: Discussionmentioning
confidence: 99%